Estrutura tegumentar de sementes de espécies arbóreas de Leguminosae e sua relação com o armazenamento - Camila Ribeiro Magalhães (2016)
Data about morphological and anatomical features of seeds are important for studying phylogenetic relationships in angiosperms and can provide ecological information referring to the taxa. In most species, the final step of seed development is desiccation and they are desiccationtolerant seeds. However, in other species, water loss is lethal to the seeds, which are dispersed with high water content (desiccation-sensitive seeds). The occurrence of these seed types is well documented for Leguminosae, a global distribution family with great ecological and economic importance. Therefore, the general aim of this study was to analyze the morphology and anatomy of eight species of the three subfamilies of Leguminosae, investigating the distinctive and similar aspects in the subfamilies and relating the structural traits to desiccation susceptibility in each subfamily. For this, mature seeds of the eight selected species were collected and grouped in two lots: fresh seeds and seeds stored for 12 months. Inga laurina (Mimosoideae) and Swartzia multijuga (Papilionoideae) have the highest water content, respectively 67.72% and 40.04%, confirming their desiccation susceptibilty. Bauhinia variegata presented larger dimensions in Caesalpinioideae, while the desiccation-sensitive species Inga laurina and Swartzia multijuga showed larger dimensions in their subfamilies. After storage, superficial changes were observed in different regions of the seeds of all species. In Bauhinia variegata, the exotesta is composed of cubic cells and the mesotesta presented parenchyma cells; Caesalpinia ferrea (Caesalpinioideae) shows the typical testa of Leguminosae. Inga laurina has a sarcotesta with long thin-walled trichomes in the exotesta and mesotesta composed by a few layers of living parenchyma cells. In Piptadenia gonoacantha and Samanea inopinata (Mimosoideae), the mesotesta consists of a few layers of parenchyma cells, which follow the pattern for the family. In Swartzia multijuga, the testa consists of periclinal compacted cells, with indistinguishable exotesta and mesotesta. Erythrina speciosa and Platypodium elegans (Papilionoideae) have the typical testa of Leguminosae. After storage, only the desiccation-sensitive seeds of Inga laurina and Swartzia multijuga had anatomical changes. Our data did not indicate any typical characteristic of each subfamily, but differences related to the type of fruit and desiccation susceptibility. Considering the scarcity of studies examining the damage produced by the storage on the seed coat structure, particularly to the desiccation-sensitive seeds, our results indicate these are interesting approaches for future work, including other families.